Une méthode de calcul de structures soumises à des chargements mobiles: Application au freinage automobile - Nguyen-Tajan, Mac-Lan; Maitournam, Habibou; Thomas, Jean-Jacques (European Journal of Computational Mechanics, 2002)
The work presented in this paper is part of a global study of the life prediction of an automotive brake disc. This component is subjected to thermomechanical loads that can generate different types of damage : honey-comb cracking, radial cracks on the rubbing surface or circonferential crack in the elbow. The numerical prediction of these phenomena needs the elaboration of numerical methods adapted to problems of structures submitted to thermomechanical moving loads. These methods consist in eulerian algorithms that are presented and described.